Assessing the use of two southwestern Atlantic estuaries by different life cycle stages of the anadromous catfish Genidens barbus (Lacépède, 1803) as revealed by Sr:Ca and Ba:Ca ratios in otoliths - Avigliano, Esteban (2015)
Fil: Avigliano, Esteban. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Unidad Ejecutora de Investigaciones En Produccion Animal; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Veterinarias. Centro de Estudios Transdisciplinarios del Agua; Argentina